Inhibitory Effects of Ginseng (Panax ginseng) Berry on Tumour Promotion and Inflammatory Ear Oedema Induced by TPA - Yasukawa, Ken; Whang, Wan-Kyunn; Ko, Sung-Kwon (Journal of Nutritional Therapeutics, 2016)
Cancer prevention is a major issue in the field of public health. Ethanol extracts of the ginseng berry were found to inhibit the inflammation induced by 12-O-tetradecanoylphorbol-13-acetate (TPA), a tumour promoter. The extracts also inhibited tumour promotion by TPA in the mouse skin two-stage carcinogenesis model. The major components, ginsenosides Rd (3) and Re (4), inhibited inflammation induced by TPA in mice, while protopanaxadiol (1) and protopanaxatriol (2), the aglycones of these ginsenosides, markedly inhibited TPA-induced inflammatory ear oedema in mice. The inhibitory effects of these compounds were more potent than those of indomethacin.